Redistributing global inequality: a thought experiment - Borocz, Jozsef (2005)
The United Nations proclaimed the period 1997-2006 as the `First United Nations Decade for the Eradication of Poverty'. The 1995 UN resolution recognised the existence of global inequalities that have deepened over time and assigned different tasks to donor (wealthy) nations and developing countries to ensure a greater equity among nations. This article focuses on the fiscal feasibility of a plan for global inequality reduction, a project that can be defined as a large-scale historic social process of social change aiming to diminish `oligarchic wealth' in favour of a less extremely unbalanced structure of distribution, that is, `democratic wealth'. The project proposes global collective action to reduce interstate inequality in per capita economic performance. A successful implementation of such a project would, however, require the construction of social and political institutions leading to political action by a majority of humankind. - Reproduced.
Keywords: Poverty; Income distribution